Intervensi Berbasis Nilai ”Bhuppa Bhabhu Ghuru Rato” untuk Menurunkan Sikap Terhadap Pernikahan Dini Pada Remaja di Silo Jember - Endah Mastuti; Maulia Gitawati Indiswari; Herdina Indrijati (I-Com: Indonesian Community Journal, 2024)
Silo sub-district faces a high rate of early marriage, with 971 cases in 2022. The head of SMPN 2 Silo also expressed concern that many students prefer to marry young rather than continue their education. Contributing factors include low student knowledge, family influence, lack of prevention support and cultural factors. To address this issue, a local values-based intervention “BHUPPA-BHABHU-GHURU-RATO” was introduced to prevent early marriage. The activity was designed to increase knowledge about the dangers of early marriage and foster attitudes against it. Activities were conducted offline using modeling, education, interactive games, and pre-test and post-test methods. The intervention results showed a decrease in support for early marriage from 54.5% to 22.2%, while opposition increased by 46.1%. This program proved to be effective in increasing knowledge and attitudes against early marriage, and can be a model for similar activities in other schools or regions.